MOTIF KEPEDULIAN LINGKUNGAN DAN KAITANNYA DENGAN PERILAKU KONSUMEN SADAR LINGKUNGAN - Kevin Juan Tanggo Laksono; Bertina Sjabadhyni (MANASA, 2012)
Inconsistent effects of the relationship between motive for environment concern and the green environment behavior occurred since motive for environment concerns are preserved as an unidimensional construct. This research uses a multidimensional approach on motive for environment concern in order to examine the relationship between each dimension of the motive with the green environment behavior. Those dimensions include egoistic, altruistic, and biospheric dimensions. Using environmental motives scale and ecological conscious consumer behavior scale, 276 college students were participating in the study. The results shown that each dimension of the motives correlates significantly with the green environment behavior. Furthermore, biospheric motive contributes the largest part to such behavior. This research has a meaningful practical implication to the green environment campaign. The campaign needs to address the specific reason behind the environment concern motive, so that it will be more effective reaching the goal of green consumers.